The Impact of Sacubitril / Valsartan Versus ACE/ARB Therapy on Functional Capacity in Heart Failure with Preserved Ejection Fraction (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Internal Medicine; Research